Long-distance trips with heavy loads: jadidism and the national movement in Crimea (Халықаралық қатынастар және халықаралық құқық сериясы, 2022)
In this study, we will try to tell about the ideals of the Crimean Jadids, which began in Bakhcherai, and then spread throughout the place inhabited by Turks. Speaking of Jadidism and Jadidists, one of the pioneers of Jadidism, the great Turkish nationalist Ismail Gaspıralı, should be noted. Ismail Gaspıralı is the founder and defender of the Usul-i Jadit schools, which gave the name to this concept. The works written about the Jadids are the works of Ismail Gaspıralı.The study of the national movement is an actual direction of modern political science. The activity of the national intelligentsia to preserve cultural identity on the territory of the Russian Empire is of direct importance in Kazakhstan's domestic science. The ideas of Jadidism were popular not only in Crimea, but also enjoyed wide popularity in Kazakhstan. The activity of Ismail Gaspıralı became a kind of catalyst for the activation of the national movement throughout the Russian Empire. On January 17, 1921, a delegation of the People's Republic of Bukhara arrived in Ankara to establish diplomatic relations during the Liberation War. The delegation presented Mustafa Kemal with three gold-embroidered swords and an iron Koran. Jadidism was the main philosophy of the new Turkish Republic.Key words: Jadidism, Islam, Panturanism, Crimea, Nationalism.